Can immersive virtual reality magnify treatment outcomes of computerized script training on Cantonese speakers with chronic aphasia? Protocol of a randomized controlled trial - Winsy Wing Sze Wong; Donald Shi Pui Li; Kenneth Ngai Kuen Fong; Peter Hiu Fung Ng; Hoi Tsz Karen Kwok (PLoS ONE, 2026)
Background Aphasia persists in 20% of the stroke population. Speech therapy has been suggested to benefit the functional communication of people with aphasia (PWA). Virtual reality (VR) has been widely applied in motor/cognitive rehabilitation of stroke patients. The current proposal investigates the efficacy of VR-based computerized script training on the functional communication of PWA. Methods A three-armed assessor-blinded randomized controlled trial (RCT) will recruit 120 PWA. They will be randomly assigned to 1) VR-based computerized script training, 2) computerized script training without VR, or 3) no treatment control. In the VR condition, PWA will practice in VR depicting everyday contexts, while in the non-VR group, PWA will practice with static photos. PWA in the control group will be assessed without training. Outcomes on functional communication, aphasia severity, and quality of life will be compared before/after treatment. The findings will provide empirical evidence to inform the development of effective and ecologically valid interventions for PWA. Trial registration ClinicalTrials.gov NCT06722092